Characterization of Small Dosimeters Used for Measurement of Eye Lens Dose for Medical Staff during Fluoroscopic Examination - Kosuke Matsubara; Sayu Yoshida; Ayaka Hirosawa; Thunyarat Chusin; Yasushi Furukawa (Diagnostics, 2021)
This study aimed to evaluate the property of small dosimeters used for measuring eye lens doses for medical staff during fluoroscopic examination. Dose linearity, energy dependence, and directional dependence of scattered X-rays were evaluated for small radiophotoluminescence glass dosimeters (RPLDs), those with a tin filter (Sn-RPLDs), and small optically stimulated luminescence dosimeters (OSLDs). These dosimeters were pasted on radioprotective glasses, and accumulated air kerma was obtained after irradiating the X-rays to a patient phantom. Strong correlations existed between fluoroscopic time and accumulated air kerma in all types of dosimeters. The energy dependence of Sn-RPLD and OSLD was smaller than that of RPLD. The relative dose value of the OSLD gradually decreased as the angle of the OSLD against the scattered X-rays was larger or lower than the right angle in the horizontal direction. The ranges of relative dose values of RPLD and Sn-RPLD were larger than that of OSLD in the vertical direction. The OSLDs showed lower doses than the RPLDs and Sn-RPLDs, especially on the right side of the radioprotective glasses. These results showed that RPLDs, Sn-RPLDs, and OSLDs had different dosimeter properties, and influence measured eye lens doses for the physician, especially on the opposite side of the patient.